Long Non-coding RNA: A Key Regulator in the Pathogenesis of Diabetic Cardiomyopathy - Guo, Yaoyao; Feng, Xiaohui; Wang, Dan; Kang, Xiaonan; Zhang, Lu; Ren, Huihui; Yuan, Gang (Frontiers in Cardiovascular Medicine, 2021)
In recent years, diabetes mellitus has become a global issue with increasing incidence rate worldwide. Diabetic cardiomyopathy (DCM), one of the important complications of diabetes, refers to patients with type 1 and type 2 diabetes who have ventricular hypertrophy, fibrosis and even diastolic dysfunction. The pathogenesis of DCM is related to oxidative stress, inflammatory response, apoptosis, autophagy, myocardial fibrosis and diabetic microangiopathy. Long noncoding RNAs (lncRNA) is a non-coding RNA with a length longer than 200 nucleotides which lack the ability of protein coding. With the development of molecular technology, massive evidence demonstrates that lncRNA play a critical role in the molecular mechanism of DCM. Moreover, it can also be used as potential diagnostic markers for DCM. In this review, we intend to summarize the pathological roles and molecular mechanism of lncRNA in the progression of diabetic cardiomyopathy, which may provide promising diagnosis and treatment strategies for DCM.